On Antimagic Labeling for Some Families of Graphs - Shawkat, Noor K.; Ahmed, Mohammed A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
Antimagic labeling of a graph with vertices and edges is assigned the labels for its edges by some integers from the set , such that no two edges received the same label, and the weights of vertices of a graph are pairwise distinct. Where the vertex-weights of a vertex under this labeling is the sum of labels of all edges incident to this vertex, in this paper, we deal with the problem of finding vertex antimagic edge labeling for some special families of graphs called strong face graphs. We prove that vertex antimagic, edge labeling for strong face ladder graph , strong face wheel graph , strong face fan graph , strong face prism graph and finally strong face friendship graph .